Karakterisasi Asam Lemak dan Aktivitas Antioksidan Minyak Hasil Ekstraksi Biji Kelor - Ayu, Lidya Risang; Aliwarga, Lienda; Adisasmito, Sanggono (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
Diversity of plants that are sources of vegetable oil grows abundantly in Indonesia, making Indonesia have potential to become a large vegetable oil-producing country. Moringa plant is one of plants predicted to have new potential as a vegetable oil-producing plant. The seeds of Moringa plant, which contain 35–40% oil, are used for various purposes such as pharmaceutical, cosmetic, and automotive industries. Saturated fatty acids contained oleic acid, palmitic acid, stearic acid, behenic acid, and arachidic acid which are beneficial for health. Moringa seed oil also contains antioxidants, antimicrobials, and vitamins C, E, B1, and B2. Oil extraction from Moringa seeds in this study used mechanical pressing method with moisture content of Moringa seeds 8 and 16% w/w. The pressing temperature varied at 80oC, 100oC, and 120oC. Characterization of fatty acid composition of Moringa seed oil was obtained by fatty acid content of 74.6–79.9% oleic acid, 5.77–7.78% palmitic acid, 4.71–5.48% stearic acid, 4.83–8.71% behenic acid, and 2.76–6.5% arachidic acid. Highest antioxidant activity was obtained at a pressing temperature of 80oC with a moisture content of 8% Moringa seeds, resulting in an IC50 value of 67.4 ppm which is included in compounds with strong antioxidant activity.